A dor que ninguém vê : “corpos docilizados” com episódios reacionais hansênicos - Pereira, Thayza Miranda (2013)
Leprosy is a stigmatized high power incapacitating disease which is partly attributed to leprosy reactional states. The relevance of this theme is the urgent need to diagnose and treat leprosy reaction episodes, acute inflammatory events in the course of a chronic, disease that can affect individuals of leprosy before, during treatment and after discharge. It aims to understand the experience of bodies with reactive episode of leprosy at the individual, family and community ambits. This is on the assumption that the reactive episodes mark the lives of people contributing to stigma and social isolation. It is a qualitative research, developed at the light of existential phenomenology. This study was set at the reference center for leprosy in the city of Floriano in Piauí. There were nine phenomenological interviews, in April 2012, with four women and five men who had or have lived such experience. To reveal the phenomenon of living with leprosy reactions, we were led to question: "What is it like, for you to have leprosy and the reactional episode presented" (considering their personal, family and community)? Thus, the subjects’ speeches were analyzed from the perspective of scholars of existential phenomenology. The analysis of descriptions led us to identify the thematic units: aching bodies - the discovery of leprosy; cracked bodies - and body transformation experience; broken bodies - the uncertainty of cure due to sequels; re-signified bodies - life changes after leprosy reaction episodes; body senses - experience in family and community; disciplined bodies - experience in the health care service. The understanding of the phenomenon culminated with the drawn assumption, allowing us to reveal some facets that mean for subject-transformations and changes in their lives, occasioned by the maintenance of leprosy reaction episodes, installed by physical disabilities and functional limitations reflected in the labor activities and Socioeconomic aspects of mundane existence, thus strengthening the social stigma that permeates leprosy / leprosy reaction episodes. It also revealed the autonomy of self-care emphasized by the knowledge of the disease and its implications, the family and community support needed in order to deal with the sickness, and the ability to reframe life producing encounters between health professionals and people affected by leprosy; considering the knowledge and practices existentially built.